Crystal structure determination by global optimisation in configuration space: a case study for distributed computing on the NRW-grid. (22nd August 2011) - Roth, G.; Bischof, C.; Eifert, Th.
The problem of ab-initio crystal structure determination from (incomplete) powder X-ray diffraction data is formulated as a global optimisation problem. The problem is of complexity class P, which suggests that the problem itself is practically infeasible for any but trivial structures. Yet, we show in this report that the inherent symmetry of the problem along with suitable heuristics and with massive computational power, allows the determination of structures with up to 20 atoms in the asymmetric unit from scratch. We give an overview of the methods employed and show numerical examples obtained by solving a model problem on the NRW-grid, which harnesses the computational power of several hundred computers at several universities in the state of Northrhine-Westfalia.